1993
DOI: 10.1210/endo.132.1.8380386
|View full text |Cite
|
Sign up to set email alerts
|

Diazepam binding inhibitor is a paracrine/autocrine regulator of Leydig cell proliferation and steroidogenesis: action via peripheral-type benzodiazepine receptor and independent mechanisms.

Abstract: Previous studies demonstrated that the polypeptide diazepam binding inhibitor (DBI) and its receptor, the peripheral-type benzodiazepine receptor (PBR), are involved in the regulation of steroid biosynthesis and that one site of PBR action resides in mitochondria. In the present investigation, evidence is presented that a functional form of PBR is also present at the cell surface. First, PBR was immunolocalized in the rat testis using biotin-streptavidin peroxidase immunocytochemistry, and results revealed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
76
0
2

Year Published

1993
1993
2002
2002

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 113 publications
(89 citation statements)
references
References 2 publications
11
76
0
2
Order By: Relevance
“…Our laboratory, as well as others, has previously shown that PBR ligands regulate cell proliferation. [7][8][9][10][11][13][14][15][16][17] The in vivo behavior of the cells, however, differs from their in vitro behavior where no differences in the rates of cell proliferation between the MDA-231 PH and PL is seen. This may be due to a minimum of PBR levels required for cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our laboratory, as well as others, has previously shown that PBR ligands regulate cell proliferation. [7][8][9][10][11][13][14][15][16][17] The in vivo behavior of the cells, however, differs from their in vitro behavior where no differences in the rates of cell proliferation between the MDA-231 PH and PL is seen. This may be due to a minimum of PBR levels required for cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Increased expression of PBR has been found in numerous tumor types and PBR has been shown to regulate the differentiation state and proliferation rates of several cancer cell lines. [7][8][9][10][11][12][13][14][15][16][17][18][19][20] Over the past several years our laboratory has examined the role of PBR in breast cancer using the MDA-231 cell line. While examining MDA-231 cells from various origins we observed variations in their PBR levels.…”
mentioning
confidence: 99%
“…Supernatant was recovered and neutrophils were isolated by Ficoll-Paque Plus density-gradient centrifugation as described [21]. Contaminating erythrocytes were eliminated by 5-min hypotonic lysis in distilled water with the following added (g/L): 8.248 NH 4 …”
Section: Cell Preparationmentioning
confidence: 99%
“…Proteolytic cleavage of DBI results in the production of several biologically active fragments (collectively known as endozepines [2]) that are involved in the regulation of multiple processes, such as mitochondrial steroid biosynthesis in adrenocortical and Leydig cells [3,4], glucose-induced insulin secretion from pancreatic islets [5], and ␥-aminobutyric acid (GABA)-induced inhibition on pituitary melanotrope cells [6]. The biological actions of DBI-derived peptides have been ascribed mainly to their ability to bind central-type benzodiazepine receptors (cBRs) located on the GABA A receptor complex [see ref .…”
Section: Introductionmentioning
confidence: 99%
“…DBI was originally purified from brain by monitoring its ability to displace diazepam from the allosteric modulatory sites for y-taminobutyric acid action on y-aminobutyric acidA receptors (11,13). DBI was found to be present in a variety of tissues (14), to be highly expressed in adrenocortical and testicular Leydig (14)(15)(16) steroidproducing cells, and to have a variety of specialized functions in different tissues (10,11,13,15,(16)(17)(18). We and others (9,10,15,16,19,20) then showed that bovine adrenal DesGly85-Ile86-DBI, rat and bovine brain native DBI, as well as rat testis native DBI stimulate intramitochondrial cholesterol transport and increase pregnenolone formation by isolated adrenocortical, Leydig, or glial-cell mitochondria.…”
mentioning
confidence: 99%